2023
DOI: 10.1038/s41586-023-05989-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the human intestinal environment under physiological conditions

Abstract: The spatiotemporal structure of the human microbiome1,2, proteome3 and metabolome4,5 reflects and determines regional intestinal physiology and may have implications for disease6. Yet, little is known about the distribution of microorganisms, their environment and their biochemical activity in the gut because of reliance on stool samples and limited access to only some regions of the gut using endoscopy in fasting or sedated individuals7. To address these deficiencies, we developed an ingestible device that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(108 citation statements)
references
References 79 publications
(112 reference statements)
1
74
0
2
Order By: Relevance
“…Also, we should note that our enzyme activity workflow can only measure the overall activity of each isozyme at a single substrate concentration, and the source of the isozyme, its gene, and its kinetic analysis deserve further attention. Moreover, our workflow was mainly based on stool samples; however, it has been reported that fecal microbiota composition does not accurately reflect the intestinal environments such as the colon ( 55 , 56 ). Therefore, our microbial-host isozyme system only simulates the activity of fecal microbiota, and the activity of different enzymes in diverse intestinal segments still needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we should note that our enzyme activity workflow can only measure the overall activity of each isozyme at a single substrate concentration, and the source of the isozyme, its gene, and its kinetic analysis deserve further attention. Moreover, our workflow was mainly based on stool samples; however, it has been reported that fecal microbiota composition does not accurately reflect the intestinal environments such as the colon ( 55 , 56 ). Therefore, our microbial-host isozyme system only simulates the activity of fecal microbiota, and the activity of different enzymes in diverse intestinal segments still needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbial BA deconjugation, catalyzed by BSHs, is critical for secondary BA metabolism in the intestines. Recent studies identified BA conjugation, which was previously thought to only occur via host-encoded enzymes, as a widespread transformation mediated by the gut microbiota to produce MCBAs. To understand the role of BSH in the deconjugation of MCBAs, we biochemically characterized the substrate preference of two representative BSHs, L. plantarum BSH1 and C.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbial enzymes can then further metabolize unconjugated BAs through epimerization and redox modifications to produce secondary BAs . Recent work demonstrated that unconjugated BAs can also be reconjugated to a wide variety of many amino acids, including tyrosine, phenylalanine, and leucine, by microbial enzymes to produce microbially conjugated bile acids (MCBAs, Figure a). As BSH activity is thought to precede all subsequent BA transformations, this enzyme has been termed the “gatekeeper” enzyme of secondary BA metabolism. , …”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, in situ studies like ours are necessary for investigating how colonization is shaped by uniquely human aspects of lifestyle and gastrointestinal anatomy, factors that are difficult to replicate in mouse models 42,80 or in vitro communities 81 . Future work that combines our approaches with barcoded strain libraries 82 or spatially resolved sampling devices 83 can further illuminate the ecological and evolutionary forces that shape colonization in the human gut.…”
Section: Discussionmentioning
confidence: 99%